Diaphragmatic Kinetics Assessment by Tissue Doppler Imaging and Extubation Outcome - Cammarota, Gianmaria; Boniolo, Ester; Santangelo, Erminio; De Vita, Nello; Verdina, Federico; Crudo, Samuele; Sguazzotti, Ilaria; Perucca, Raffaella; Messina, Antonio; Zanoni, Marta; Azzolina, Danila; Navalesi, Paolo; et al. (Respiratory care, 2021)
The assessment of diaphragmatic kinetics through tissue Doppler imaging (dTDI) was recently proposed as a means to describe diaphragmatic activity in both healthy individuals and intubated patients undergoing weaning from mechanical ventilation. Our primary aim was to investigate whether the diaphragmatic excursion velocity measured with dTDI at the end of a spontaneous breathing trial (SBT) was different in subjects successfully extubated versus those who passed the trial but exhibited extubation failure within 48 h after extubation. We enrolled 100 adult subjects, all of whom had successfully passed a 30-min SBT conducted in CPAP of 5 cm H O. In cases of extubation failure within 48 h after liberation from invasive mechanical ventilation, subjects were re-intubated or supported through noninvasive ventilation. dTDI was performed at the end of the SBT to assess excursion, velocity, and acceleration. Extubation was successful in 79 subjects, whereas it failed in 21 subjects. The median (interquartile range [IQR]) inspiratory peak excursion velocity (3.1 [IQR 2.0-4.3] vs 1.8 [1.3-2.6] cm/s, < .001), mean velocity (1.6 [IQR 1.2-2.4] vs 1.1 [IQR 0.8-1.4] cm/s, < .001), and acceleration (8.8 [IQR 5.0-17.8] vs 4.2 [IQR 2.4-8.0] cm/s , = .002) were all significantly higher in subjects who failed extubation compared with those who were successfully extubated. Similarly, the median expiratory peak relaxation velocity (2.6 [IQR 1.9-4.5] vs 1.8 [IQR 1.2-2.5] cm/s, < .001), mean velocity (1.1 [IQR 0.7-1.7] vs 0.9 [IQR 0.6-1.0] cm/s, = .002), and acceleration (11.2 [IQR 9.1-19.0] vs 7.1 [IQR 4.6-12.0] cm/s , = .004) were also higher in the subjects who failed extubation. In our setting, at the end of SBT, subjects who developed extubation failure within 48 h after extubation experienced a greater diaphragmatic activation compared with subjects who were successfully extubated. (ClinicalTrials.gov registration NCT03962322.).